The Influence Cash Position Analysis over Debt to Equity Ratio, Return On Assets, And Inventory Turnover on Dividend Payout Ratio: Consumer Goods Companies in Indonesia Stock Exchange 2012-2017 Case Study - Roisyam Azmal; Dimas Angga Negoro; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2019)
Dividend policy is the most controversial topic in the context of corporate finance, where the variables that influence it are still uncertain in the literature. This study aims to analyze the effect of cash position, debt to equity ratio, return on assets and inventory turnover to the dividend payout ratio, as well as providing information and description to investors whose investment objectives to pursue dividends based on variables. Here, we analyze the panel data regression over 11 consumer goods industries in the Indonesia Stock Exchange from 2012 to 2017. The results shows that the variable return on assets and inventory turnover had a positive and significant effect on the dividend payout ratio, and also the debt to equity ratio had a negative and significant effect on the dividend payout ratio. While the cash position had not significantly affect on the dividend payout ratio